Implementasi Data Mining Penjualan Kosmetik Pada Toko Kazana Menggunakan Metode Algoritma Hast Based - Annisa Fadillah Siregar; Rizkah Fadilllah; Miya Andriyani (Bulletin of Multi-Disciplinary Science and Applied Technology, 2021)
As you know, every woman really wants beauty or beauty in something, especially beauty in herself. In general, everyone already knows that what can make a woman physically beautiful is cosmetics. Sales of cosmetic tools such as lipstick, powder, or other tools. Items like this are often purchased by women in general. Tools in cosmetics can change the appearance of an ordinary woman in general to be extraordinary. Many items or cosmetic equipment purchased by women cannot be separated from the calculation of data on each sale of cosmetic equipment. Here we will find out how to calculate sales of cosmetic equipment data. The right way to find out the calculation of cosmetic tools is by using the Hash Based Algorithm. In this Hash Based Algorithm there is a minimum support value, minimum confidence value and amount of data. By using the Hash Based Algorithm we can find out the calculation or amount of data on cosmetic sales correctly. After 3 iterations, 1 address remains in the hash table with 3-itemset. Obtained frequent itemset for 3-itemset, namely (Face Cleanser, Nail Polish, Eyeshadow) with support count = 2